Nanostructured polysaccharide-based materials obtained from renewable resources and uses - Badiei M.; Asim N.; Mohammad M.; Akhtaruzzaman M.; Samsudin N.A.; Amin N.; Sopian K. (Elsevier, 2023)
Polysaccharides are renewable and biodegradable polymers that possess varieties of functional groups such as carboxyl, hydroxyl, and amino groups. Being high reactive, these functional groups allow modification of polysaccharides with various molecules to prepared building blocks for synthesis of different types of composites for various applications. This chapter reviews recent progress in development of types of polysaccharide-based nanocomposites. In the context of applications, the focus is on edible food packaging, water treatment as well as energy conversion and conservation systems that comprehensively are illustrated. 2022 Elsevier Inc. All rights reserved.